Design and Performance Testing of Semi-Automatic Machine for Potato Peeler-Cutter - Didik Sugiyanto; Resma Adi Pangestu; Yefri Chan; Aep Saepul Uyun (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
In processing potatoes into sticks on a large scale, an equipment is needed that can facilitate the manufacturing process. Therefore, it is necessary to research the design of the potato peeler and cutter and test the performance of the tool. This study aims to determine the design and selection of materials, to determine the production process of potato peeler and cutter and to determine the effect of rotation on time and level of cleanliness of potatoes. This machine consists of several components, namely the frame, peeler tube, cutting tube, transmission unit and electric motor. The working mechanism of this tool is that the peeler disc which is moved by an electric motor rotates to push the potatoes, so that the rotation causes friction between the potatoes and the peeler tube which has a rough surface, this friction causes the potato skin to peel off and is then forwarded to the potato cutter tube with a propeller, which is driven by an electric motor so that the rotation pushes the potatoes into the knife so that the potatoes that pass through the peeler tube are cut into sticks. From the results of testing the tool obtained data on potatoes grade A with an average time of 2 minutes and a motor rotation of 170 rpm, capable of peeling 96.8% of potatoes with a weight loss of 3.2% of potatoes. For potatoes grade B with an average time of 2 minutes and a motor rotation of 170 rpm was capable of peeling 97% of potatoes with a weight loss of 3%, and the results of potato cuts with a cross sectional size of 6.9 × 6.9 mm.Keywords:   french fries, peeler, cutter, potato stick